(untitled) (Global Journal of Medical Research, 2014)
We report the first case of concomitant C. laurentii and M. tuberculosis pulmonary infection in a non-immunocompromised patient caused by a multiresistant C.laurentii strain and the fourth reported case of C.laurentii pulmonary infection up to now. We review the literature regarding C. laurentii pulmonary infections as well as its treatment.